Key ultrasound predictors in the prenatal assessment of congenital pulmonary airway malformation: a single-center experience - Fabietti, Isabella; Novak, Alice; Valfrè, Laura; Vassallo, Chiara; De Rose, Domenico Umberto; Viggiano, Milena; Conforti, Andrea; Iacusso, Chiara; Bonito, Marco; Bagolan, Pietro; Caforio, Leonardo (Frontiers in Pediatrics, 2025)
BackgroundThis study assesses the sensitivity and specificity of congenital pulmonary airway malformation (CPAM) Volume Ratio (CVR) in predicting the need for fetal therapy (FT) and explores the role of additional ultrasound indicators, including the Observed/Expected Lung to Head Ratio (O/E LHR) and Mediastinal Angle Shift (MSA), in improving FT prediction.MethodsWe retrospectively studied all CPAM cases referred to our Center from 2018 to 2022. FT was provided at any CVR value in cases of hydrops, rapid lesion growth, or polyhydramnios. The worst CVR, O/E LHR, and MSA values between 20 and 28 weeks of gestation were analyzed.ResultsAmong 62 CPAM cases, 56.4% right-sided and 43.5% left-sided. Hydrops occurred in 5 cases, all right-sided. FT was required in 14 cases (11 receiving steroids and 3 thoraco-amniotic shunt). CVR was significantly higher in the FT group compared to the non-FT group (p < 0.0001), with an optimal cut-off of 1.25 (Sn 100%; Sp 89.6%) for predicting FT. The O/E LHR was significantly lower in the FT group (mean 44.8 vs. 58.3; p = 0.0046, AUC 0.75), with a Sn of 84% and Sp of 62%. MSA was significantly higher in the FT compared to the non-FT group (p < 0.0001), with a threshold of 13.3° providing high Sn (92.8%) and Sp (89.3%) for predicting FT.ConclusionsCVR is the most reliable predictor of the need for FT, even at lower thresholds. MSA can effectively complement CVR in predicting FT, and using multiple parameters may improve parental counseling and identify cases needing closer monitoring.